A framework for buyers’ house selection criteria vs. post-occupancy residential satisfaction levels in North Cyprus - Egemen, Mehmedali (International Journal of Strategic Property Management, 2021)
Intense competition existing in speculative house-building market creates an industry dominated by client groups. This paper provides insights into house-buyers’ perceptions of a set of criteria contributing to their selection of the product (house) to buy together with the post-occupancy residential satisfaction levels reached after their selections, by presenting survey findings of 320 house-buyers in North Cyprus house-building market. A striking finding was the fact that the responding house-buyers belonging to different categories had very significantly different priorities in the house selection stage. Therefore, market segmentation is the area with a great potential for competitive advantage which will help the house-builders to focus on the product selection criteria of buyers in specific segments so that the capabilities and the strategies of the company can be presented in ways best suited to take advantage of these. Furthermore, the findings demonstrated that price/payment method, design and customization were all crucially important for the buyers. Therefore, builders should focus on determining the optimum customization to offer greater product choice and a proper design without losing their competitive prices. The post-occupancy residential satisfaction values varied significantly according to the categories of house-buyers. This study will combine house-buyers’ product selection criteria and the related satisfaction levels reached during post-occupancy stage. Although this study was based on input provided by house-buyers in North Cyprus market, we believe the findings are of good value to builders and buyers in other similar markets.First published online 26 October 2020